The Social Construction of Female Futsal Players in Surabaya - Anas, Fahmi (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
Women face many barriers, discrimination, and stereotypes to participate in a worldwide sport. This research aims to figure out the social construction of women's futsal players on futsal by using Peter L. Berger’s theory of social construction. Women stuck in the cultural taboos that prevent them from freely involved in futsal. Society in general often sees women as aliens in futsal. In the patriarchal society of Indonesia, futsal is seen to be suitable for men, but not for women. This research is qualitative research involving a descriptive analysis. Data were collected through interviews and observations. This research was conducted in Surabaya with female futsal players as the informants. The findings indicated several variations of the social construction of female futsal players through a process of objectification, dialectics externalization, and internalization on futsal. Female futsal players disagreed with the identification of sports with men.